Empowerment of farmer groups training on multiplication of liquid organic fertilizer with nitrobacter in Dawung Village, Matesih District: Pemberdayaan kelompok tani pada pelatihan perbanyakan pupuk organik cair dengan nitrobacter di Desa Dawung Kecamatan Matesih - Zahwa Ariya Saputra; Widhoyoko , Yudhistiro Pandu (JAKADIMAS (Jurnal Karya Pengabdian Masyarakat), 2025)
Currently, rice remains the staple food and primary source of carbohydrates for nearly the entire population of Indonesia. As time goes on, the human population continues to grow. However, rice stocks in Indonesia remain limited, necessitating rice imports from abroad. On the other hand, farmers' access to chemical fertilizers has become increasingly difficult to obtain. The objective of this community service activity is to provide training to farmers in the production of liquid organic fertilizer. The target audience for this community service activity is rice farmers in Dawung Village, Matesih Subdistrict, Karanganyar Regency, Central Java. The training on the production of liquid organic fertilizer using Nitrobacter is highly beneficial for farmers, particularly as an alternative to urea fertilizer, which is essential for rice plants due to its nitrogen (N) content. The training method involved both theoretical instruction and hands-on fertilizer production with the participating farmers. The results of the activity showed that the farmers were pleased with the initiative, evident from their enthusiasm to participate in the activity during fertilizer production. Another indicator was the numerous questions raised by farmers regarding modifications to both the raw materials and the production process.